2009
DOI: 10.1002/dc.21011
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic diagnosis of pulmonary adenocarcinoma with micropapillary pattern: Does it correlate with the histologic findings?

Abstract: Micropapillary adenocarcinoma is associated with poor-prognosis in several organs including the lung. The presence of small tight balls of neoplastic cells devoid of fibrovascular core in cytological preparations (micropapillary tufts) has been described as characteristic of micropapillary adenocarcinoma. In the lung, however, this criterion has not been validated. The cytological material of 46 cases of histologically proven pulmonary adenocarcinoma with a micropapillary component was compared to 33 cases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 38 publications
12
34
0
Order By: Relevance
“…It has been recently reported that there is no correlation of histologic patterns and cytologic patterns seen in aspiration biopsies of lung adenocarcinomas. 29 In core biopsies, limited sampling of the tumors may not be representative of the heterogeneity of the primary tumor. Therefore, the scoring system must be validated in these small samples or a modified scoring system that includes nuclear grade could be applied to smaller tissue samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently reported that there is no correlation of histologic patterns and cytologic patterns seen in aspiration biopsies of lung adenocarcinomas. 29 In core biopsies, limited sampling of the tumors may not be representative of the heterogeneity of the primary tumor. Therefore, the scoring system must be validated in these small samples or a modified scoring system that includes nuclear grade could be applied to smaller tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we defined micropapillary pattern, which is not specified as a distinct subtype in the 2004 WHO classification, as small papillary tufts (morule-like clusters) of neoplastic cells without a fibrovascular core seen mostly as detached clusters from the surrounding tumor, similar to earlier studies. 18,29 Comprehensive histologic subtyping was performed in the primary tumor in a semiquantitative manner with the percentage of the 5 possible tumors histologic subtypes quantified in 10% increments, totaling 100% per tumor as described earlier. 21 Predominant pattern and second most predominant pattern in a mixed-type adenocarcinoma were defined as the histologic subtypes that comprised the highest and second highest percentage(s) of a particular tumor.…”
Section: Histologic Evaluationmentioning
confidence: 99%
“…And reactive type II pneumocytes (RPII) undergo hyperplasia and reactive changes in response to injury resulting from various conditions, such as infections, interstitial lung diseases, organizing pneumonia, pulmonary drug toxicity, and tuberculosis (10,(15)(16)(17). A lepidic pattern of AC may be observed in small biopsy specimens but is difficult to diagnose in cytological material (18,19). In the aforementioned situations, it is challenging for cytopathologists to arrive at correct diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The most specific criteria, such as papillary structures, may not be present in a large number of samples. Much of this disagreement may be due to sampling, as secondary and tertiary patterns on resection may be overrepresented in a given small sample [8,9]. Some promising efforts to grade cytology samples suggest that prognostication may be part of future classifications [10].…”
Section: Introductionmentioning
confidence: 99%